Structural and photoluminescence studies on europium-doped lithium tetraborate (Eu:Li2B4O7) single crystal grown by microtube Czochralski (μT-Cz) technique *Project supported by the Department of Science and Technology–Science and Engineering Research Board (Grant No. SR/S2/LOP-0012/2011), the Government of India for Awarding Major Research Project, the University Grants Commission–Department of Atomic Research–Consortium for Scientific Research (Grant No. CSR–KN/CSR–63/2014–2015/503), and the Kalpakkam and Indore, India. (31st March 2016) - Kumaresh, A; Arun Kumar, R; Ravikumar, N; Madhusoodanan, U; Panigrahi, B S; Marimuthu, K; Anuradha, M
Abstract: Rare earth europium (Eu 3+ )-doped lithium tetraborate (Eu:Li2 B4 O7 ) crystal is grown from its stoichiometric melt by microtube Czochralski pulling technique (μT-Cz) for the first time. The grown crystals are subjected to powder x-ray diffraction (PXRD) analysis which reveals the tetragonal crystal structure of the crystals. UV–vis–NIR spectral analysis is carried out to study the optical characteristics of the grown crystals. The crystal is transparent in the entire visible region, and the lower cutoff is observed to be at 304 nm. The existence of BO3 and BO4 bonding structure and the molecular associations are analyzed by Fourier transform infrared (FTIR) spectroscopy. The results of excitation and emission-photoluminescence spectra of europium ion incorporated in lithium tetraborate (LTB) single crystal reveal that the observations of peaks at 258, 297, and 318 nm in the excitation spectra and peaks at 579, 591, 597, 613, and 651 nm are observed in the emission spectra. The chromaticity coordinates are calculated from the emission spectra, and the emission intensity of the grown crystal is characterized through a CIE 1931 (Commission International d'Eclairage) color chromaticity diagram.